2011
DOI: 10.1007/s11357-011-9316-3
|View full text |Cite
|
Sign up to set email alerts
|

The dominant human conjunctival epithelial CD8αβ+ T cell population is maintained with age but the number of CD4+ T cells increases

Abstract: The conjunctiva is a highly specialized ocular mucosal surface that, like other mucosa, houses a number of leukocyte populations. These leukocytes have been implicated in age-related inflammatory diseases such as dry-eye, but their phenotypic characteristics remain largely undetermined. Existing literature provides rudimentary data from predominantly immunohistochemical analyses of tissue sections, prohibiting detailed and longitudinal examination of these cells in health and disease. Using recovered cells fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
(37 reference statements)
3
16
0
Order By: Relevance
“…1C). Our results are consistent with an earlier study, which reported a preponderance of CD8 + T EM cells in the ocular surfaces of a cohort of human volunteers in the UK13.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1C). Our results are consistent with an earlier study, which reported a preponderance of CD8 + T EM cells in the ocular surfaces of a cohort of human volunteers in the UK13.…”
Section: Resultssupporting
confidence: 93%
“…The mucosa covering the avascular corneal surface at the visual axis contains mainly myeloid and dendritic cells, while the conjunctiva over the remainder of the ocular surface also contains lymphatics, diffuse and aggregated lymphocytes1314. While T cell subsets have been described in the conjunctiva13, the relative proportions of T RM and recirculating T cells at this barrier surface have not been studied in humans or animal models. Such information could provide insights into ocular surface inflammation.…”
mentioning
confidence: 99%
“…8 While these studies did not examine ocular disease, earlier studies have identified corneal CD8 þ T cells with epithelial vacuolation in a patient with TEN, 9 and a predominant CD8 þ T-cell population in healthy human conjunctival epithelium. 12,25 In our current study, we found that conjunctival CD8 þ and NK þ populations were not significantly elevated in SJS-TEN compared with healthy controls and this remained unchanged over time. This discrepancy might be explained by the fact that SJS-TENinduced damage is thought to be mediated by granulysin rather than the extent of cytotoxic cellular infiltrate.…”
Section: Discussionmentioning
confidence: 38%
“…11,12 Briefly, conjunctival cells were collected from the superior bulbar conjunctiva with autoclaved synthetic membranes (Supor 200; Pall Corporation) divided into two semicircles (measuring 13 3 6.5 mm 2 each). 11 Conjunctival OSIC was performed with four semicircle membranes per eye and before the application of topical fluorescein drops for clinical examination.…”
Section: Sample Collection and Laboratory Analysismentioning
confidence: 99%
See 1 more Smart Citation